Effect of solvent pretreatments on trans-dentinal cytotoxicity of bioactive materials - Salim, Ikram Aqel; Stape; Thiago Henrique Scarabello; Seseogullari-Dirihan, Roda; Mutluay, Mustafa Murat; Tezvergil-Mutluay, Arzu (Japanese Society for Dental Materials and Devices, 2026)
This study evaluated the effect of solvent-based dentin pretreatments containing dimethyl sulfoxide (DMSO) and/or ethanol on trans-dentinal cell viability of bioactive materials in simulated deep clinical cavities. Dentin discs (300 μm) were prepared, balanced among groups according to dentin permeability and autoclaved. Three-dimensional cultures of odontoblast-like cells were transferred to the pulpal aspect of dentin discs inside perfusion split-chambers designed for trans-dentinal cytotoxicity test following ISO 7405 standards. Dentin pretreatments were composed of ethanol (EtOH), DMSO, their 50% (v/v) aqueous dilutions and 50% (v/v) DMSO/EtOH. Pretreatments (1.5 μL) were applied on cell-seeded dentin discs and a 1-mm increment of one of three bioactive materials: a light-curable methacrylate-based silicate (TheraCal), a mineral trioxide aggregate (MTA) or an experimental pre-reacted glass-ionomer filler (S-PRG). Cell viability was analyzed spectrometrically according to the MTT test and cytotoxicity levels were classified following ISO 7405. TheraCal was considered severely cytotoxic, MTA moderately cytotoxic and S-PRG non-cytotoxic. Assessment of cell damage by solvents was ranked as EtOH=EtOH/H2O>DMSO>DMSO/EtOH=DMSO/H2O. The light-curable methacrylate-based silicate was the only material with considerable trans-dentinal cytotoxicity. While ethanol was harmful to odontoblast-like cells, DMSO had a minor role in cytotoxic responses used alone or combined to bioactive materials. Solvents must be considered for safe use during vital-pulp therapy.